Efficacy of different dosages of common uric acid-lowering medications in gout patients: a network meta-analysis of randomized control trials - Zheng, Xiaojia; Xie, Cunxiang; Fang, Jinying; Huang, Zhenghui; Huang, Jian; Zhao, Luming; Ye, Guancheng; Wang, Hailong (Frontiers in Pharmacology, 2025)
PurposeUrate lowering therapy (ULT) is extensively utilized for managing patients with gout. This study aims to compare the efficacy of different ULTs on serum uric acid (SUC) levels, gout flares, and adverse events (AEs) in gout patients.MethodsStudies comparing the efficacy of febuxostat, allopurinol, benzbromarone, and topixostat with placebo were searched up to March 2024. Stata 15.1 and R software 4.2.3 were employed to rank the efficacy of each ULT.ResultsThis study included 30 studies, involving 20,040 patients. All ULTs resulted in notably lower SUC levels compared to placebo/no ULT. Febuxostat 120 mg markedly reduced SUC levels compared to allopurinol and benzbromarone 25 mg (mean difference = 2.16, 95% confidence interval [0.27, 4.06], P < 0.05). Allopurinol 200/300 mg was the best choice to reduce gout flares. In terms of AEs, the allopurinol group (300 mg) had the lowest incidence of cardiovascular and renal abnormalities. Moreover, the incidence of AEs was observed to rise with increasing doses. Future well-designed randomized control trials are required to further confirm these findings.ConclusionThe study results indicate that febuxostat is the most effective ULT drug to treat gout. It can effectively help gout patients reduce SUC levels. Researchers should pay attention to the safety of drug doses.